A educação ambiental como instrumento de transformação ética e como possibilidade de direcionamento de consumo - Batista, Ildemar (My University, 2014)
Contemporary society is experiencing an environmental crisis started since the late modern age and outcome of the economic model (capitalism), that in spite of having served the driver of technological and scientific development, has led to environmental degradation, giving rise to environmental movements. One of the factors that inspires care is the new conception of social relations, called post-modernity, according to which what matters is the present, absorbing the maximum resources available at the moment without worrying about the future consequences. It also appears that there is a reluctance to accept voluntary standards regarding the environment by society, revealing a gap between the world of facts in the legal world, which translates into ineffectiveness of environmental standards. Important to consider the problem of binge drinking which, together with the production of goods, is one of the pillars of the capitalist system. However, it appears that the true essence of capitalism is to serve as access to economic power, ie, the company follows the rules dictated by the capitalist system because they crave power. So the crucial question is to find a way to work within the logic of the capitalist system, reversing the unfavorable situation for the environment. One of the tools to succeed in this business is environmental education. Making a historical review, a constitutional perspective, education has evolved over the history of Brazil, being considered as a right and a fundamental guarantee. The national legislation of environmental education, compared to the laws of Argentina, shows up much more structured and has been positively valued the National Environmental Education. Environmental education is an instrument of ethical transformation in the sense of changing paradigms, considering man as part of nature, but without denying the rationality that distinguishes it from other living beings. Environmental education, changing the way society views nature, by natural consequence, alters the pattern of consumption, driving the market and the capitalist system itself to produce consumer goods that do not harm the environment, contributing to an ecologically balanced.
A sociedade contemporânea esta vivenciando uma crise ambiental iniciada desde o final da idade moderna e resultado do modelo econômico seguido (capitalismo), que, em pese ter servido de mola propulsora do desenvolvimento tecnológico e científico, acarretou a degradação ambiental, fazendo surgir movimentos ambientalistas. Um dos fatores que inspira cuidados é a nova concepção das relações sociais, denominada pós-modernidade, segundo a qual o que interessa é o presente, absorvendo o máximo de recursos disponível no momento sem se preocupar com as consequências futuras. Verifica-se também que há uma relutância à aceitação voluntária das normas relativas ao meio ambiente pela sociedade, revelando um descompasso entre o mundo dos fatos com o mundo jurídico, o que se traduz na inefetividade das normas ambientais. Importante considerar o problema do consumo desenfreado que, aliado à produção de bens, é um dos pilares do sistema capitalista. Contudo, verifica-se que a verdadeira essência do capitalismo está em servir de acesso ao poder econômico, ou seja, a sociedade segue as regras ditadas pelo sistema capitalista porque almeja o poder. Então a questão crucial é encontrar uma maneira de trabalhar dentro da própria lógica do sistema capitalista, invertendo a situação desfavorável ao meio ambiente. Um dos instrumentos capazes de alcançar êxito nessa empresa é a educação ambiental. Fazendo um resgate histórico, numa perspectiva constitucional, a educação vem evoluindo ao longo da história do Brasil, sendo considerada como direito e garantia fundamental. A legislação de educação ambiental nacional, comparada à legislação da Argentina, mostra-se bem mais estruturada, tendo sido positivada a Política Nacional de Educação Ambiental. A educação ambiental é um instrumento de transformação ética, no sentido de mudança de paradigmas, considerando o homem como parte da natureza, mas sem negar a racionalidade que o diferencia dos outros seres vivos. A educação ambiental, modificando a forma com que a sociedade vê a natureza, por consequência natural, altera a forma de consumo, direcionando o mercado e o próprio sistema capitalista a produzirem bens de consumo que não agridam o meio ambiente, contribuindo para um meio ambiente ecologicamente equilibrado.
Keywords: Direito ambiental; Educação ambiental; Meio ambiente - Degradação ambiental; Economic power; Consumerism; Effectiveness